Watch, the Superdog! - Warner, Gertrude Chandler; Nang Chan Yeema (United States of America Albert Whitman& Company, 2004)
Benny decides to enter his dog Watch in the local pet parade, but Watch ruins his costume while saving a nest of baby birds from a cat.
Keywords: Story Collection